Polyaza macroligands as potential agents for heavy metal removal from wastewater - Elizondo Martínez, Perla; Nájera Martínez, Blanca; Pérez Rodríguez, Nancy; Reyes Hinojosa, Laura; Gómez del Río, Isabel (2013)
Two polyaza macroligands N,N´-bis(2-aminobenzyl)-1,2-ethanediamine (L1) and 3,6,9,12-tetraaza-4(1,2),11(1,2)-dibenzo-1(1,3)-pyridinacyclotridecaphane (L2) were characterized and investigated for their metal ion extraction capabilities. The nature of all complexes was established by spectroscopic techniques. The equilibrium constants were determined by spectrophotometric and potentiometric techniques and the residual concentration of metals in the solutions by atomic absorption spectrometry (AAS). The capacity of the ligands to remove heavy metals such as Cu(II), Ni(II), Cd(II), Zn(II) and Pb(II) as insoluble complexes was evaluated in wastewater from industrial effluents. These agents showed high affinity for the studied metals. The values of the equilibrium constants of the isolated complexes (between 1×104 and 2×107) demonstrated the feasibility of applying these chelating agents as alternatives for the removal of heavy metals from industrial effluents.